2021
DOI: 10.1186/s12872-021-01889-8
|View full text |Cite
|
Sign up to set email alerts
|

The stress hyperglycaemia ratio is associated with left ventricular remodelling after first acute ST-segment elevation myocardial infarction

Abstract: Background Left ventricular negative remodelling after ST-segment elevation myocardial infarction (STEMI) is considered as the major cause for the poor prognosis. But the predisposing factors and potential mechanisms of left ventricular negative remodelling after STEMI remain not fully understood. The present research mainly assessed the association between the stress hyperglycaemia ratio (SHR) and left ventricular negative remodelling. Methods We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
(44 reference statements)
2
7
0
Order By: Relevance
“…We also found a significant correlation between SHR and NT-proBNP, cTnT, and LVEF, which may contribute to an increased risk of MACE to some extent. Several clinical studies have confirmed such results among MI patients, which reported that SHR had a significant correlation with myocardial injury as shown by high peak cTnT and peak CK-MB values and their association with the severity of CAD (assessed by the Gensini score and Syntax score) [10,35,38]. On the other hand, we found that inflammatory marker such as CRP was higher among the high SHR group, which may also be associated with some unfavorable outcomes.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We also found a significant correlation between SHR and NT-proBNP, cTnT, and LVEF, which may contribute to an increased risk of MACE to some extent. Several clinical studies have confirmed such results among MI patients, which reported that SHR had a significant correlation with myocardial injury as shown by high peak cTnT and peak CK-MB values and their association with the severity of CAD (assessed by the Gensini score and Syntax score) [10,35,38]. On the other hand, we found that inflammatory marker such as CRP was higher among the high SHR group, which may also be associated with some unfavorable outcomes.…”
Section: Discussionsupporting
confidence: 83%
“…The prospective, nationwide, multi-center China AMI registry results demonstrated a significant positive correlation between SHR and long-term death in patients with AMI [ 34 ]. Numerous clinical studies have also indicated a link between SHR and unfavorable outcomes in AMI patients [ 21 , 22 , 35 , 36 ]. Pasquale et al also found that SHR significantly increases the risk of rehospitalization among 2,874 patients with ischemia with non-obstructive coronary arteries [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…[33] In Lamblin's study [33], DM was an independent predictor of cardiovascular death or rehospitalization for HF during 1-year follow up. Since stress hyperglycemia presents as an independent predictor for adverse left ventricular remodelling, Shuai et al [34] suggest this non-invasive parameter may be used to estimate its risk.…”
Section: Discussionmentioning
confidence: 99%
“…Malglycemia (the collective of absolute hypoglycemia, relative hypoglycemia, and hyperglycemia) is driven by both increases and decreases from preadmission glycemia across the admission. 13,14,22,[24][25][26][27][28][29][30][31] Compared with a single point at admission, a metric assessing malglycemia across the entire admission may provide superior insight into the nature of malglycemia. In recognition of the bidirectional nature of malglycemia over the course of an entire admission, we use the term Glycemic Ratio (GR).…”
mentioning
confidence: 99%
“…Anemia may affect HbA1c and it is unknown whether this significantly affects the prognostic ability of SHR. 35 The association of elevated SHR with mortality has been previously investigated in both the critical care setting 23 and other clinical settings, 22,[24][25][26][27][28][29][30][31] and consistently displays superior prognostic insight compared with BG. However, this does not address the association of glucose control across the entirety of the ICU admission with mortality.…”
mentioning
confidence: 99%